Treatment Of Acid Drainage In A Uranium Deposit By Means Of A Passive System - S. N. Groudev (Society for Mining, Metallurgy & Exploration, 2006)
Acid mine drainage waters generated in the uranium deposit Curilo, Bulgaria, were treated by means of a pilot-scale passive system consisting of an alkalizing limestone drain, a permeable multibarrier for microbial dissimilatory sulphate reduction, biosorption and chemical neutralization, and a natural wetland, connected in a series. The waters had pH in the range of about 2.5 ? 4.1 and contained radionuclides (uranium, radium), heavy metals (copper, zinc, cadmium, lead, nickel, cobalt, iron, manganese), arsenic and sulphates in concentrations usually much higher than the relevant permissible levels for waters intended for use in the agriculture and/or industry. The water flow rate through the passive system varied in the range of about 5 ? 15 m3/24 h, reflecting water residence times of about 60 to 20 hours. An efficient removal of pollutants was achieved by this system during the different climatic seasons, even during the cold winter days at external air and water temperatures close to 0°C. The removal was connected with different mechanisms but the microbial sulphate reduction played the main role during the warmer months of the year. However, during the cold winter days the removal of pollutants was due mainly to their sorption by the solid dead plant biomass (cow manure, plant compost, straw) present in the multibarrier as well as to their precipitation as a result of chemical neutralization caused by crushed limestone.